2022
DOI: 10.32604/jrm.2022.017373
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Bending Properties of Grouting Butt Joints Reinforced by Steel Plate Embedded in Bamboo Tube

Abstract: The construction of grouting butt joints of bamboo tubes is simple and efficient. However, when the joint is bent, the low tensile strength of the mortar easily leads to cracking of the mortar prior to the failure of the bamboo tube. In this paper, a comparative test of the bending capacity was performed on grouting butt joints reinforced by nonperforated, fully perforated, and semiperforated steel plates embedded in bamboo tubes to obtain the loaddisplacement curves and ultimate bearing capacity of various sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The flexural strength significantly differs when bamboo species are compared because the f value of 2.933 is greater than the f critical value of 2.092, tested at a significance level. This implies that the bamboo's flexural strength depends on its spices and treatment of bamboo culm and treatment period; however, the concrete infill Huang, T., & Zhuo, X. (2022) significantly increased its flexural strength of the bamboo Culm subjected to Midspan loadings Weifeng, Z. et al (2012), Table 4: ANOVA: Comparison between the flexural strength of bamboo culm as a beam infill with concrete when untreated (kiln dried), treated with seawater, and treated with seawater plus a 10 percent solution of mango polyphenol.…”
Section: Resultsmentioning
confidence: 99%
“…The flexural strength significantly differs when bamboo species are compared because the f value of 2.933 is greater than the f critical value of 2.092, tested at a significance level. This implies that the bamboo's flexural strength depends on its spices and treatment of bamboo culm and treatment period; however, the concrete infill Huang, T., & Zhuo, X. (2022) significantly increased its flexural strength of the bamboo Culm subjected to Midspan loadings Weifeng, Z. et al (2012), Table 4: ANOVA: Comparison between the flexural strength of bamboo culm as a beam infill with concrete when untreated (kiln dried), treated with seawater, and treated with seawater plus a 10 percent solution of mango polyphenol.…”
Section: Resultsmentioning
confidence: 99%
“…In the German-Chinese House at the Shanghai World Expo 2010 [12], the joints are made of prefabricated steel parts with grouting, and the prefabricated steel components are capable of connecting bamboo tubes in different directions. Huang et al [13] proposed a bamboo tube joint using grouting and built-in steel sheet connection, and the tests showed that this type of joint has high load-bearing capacity. These improved grouted joints showed better mechanical properties, but the grouting significantly increased the self-weight of the structure and could not take advantage of the light weight of the bamboo tube structure.…”
Section: Introductionmentioning
confidence: 99%
“…1, Villegas et al [15] used steel hoop, U-shaped steel splint and bolts to realize the multi-angle connection between the chords and girders in the bamboo truss structure, and tested the bearing capacity of the bamboo truss under this connection mode through static tension tests. Huang et al [16] showed the construction of grouting butt joints of bamboo tubes by adding a semi-perforated steel plate inside, pasting a CFRP sheet on the external wall and increasing the width of the steel plate is simple and efficient. Wang et al [17] proposed dowel-type bamboo joints for prefabricated bamboo structures.…”
Section: Introductionmentioning
confidence: 99%